Jak Inhibitors Modulate Production of Replication Competent Zika Virus in Human Hofbauer, Trophoblasts, and Neuroblastoma cells - Christina Gavegnano; Leda C. Bassit; Bryan D. Cox; Hui-Mien Hsiao; Erica L. Johnson; Mehul Suthar; Rana Chakraborty; Raymond F. Schinazi (Case Western Reserve University, 2017)
Zika Virus (ZIKV) is a Flavivirus that has been implicated in brain deformations, birth defects, and microcephaly of unborn fetuses and associated with Guillain-Barre syndrome.  Mechanisms responsible for transmission of ZIKV across the placenta to the fetus are incompletely understood.  Herein, we define key events modulating infection in clinically relevant cells, including primary placental macrophages (human hofbauer cells; HC), trophoblasts, and neuroblastoma cells. Consistent with previous findings, HC and trophoblasts are permissive to ZIKV infection. Decrease of interferon signaling by Jak 1/2 inhibition (via ruxolitinib) significantly increased ZIKV replicationin HC, trophoblasts, and neuroblasts. Enhanced ZIKV production in ruxolitinib treated HC was associated with increased expression of HLA-DR and DC-SIGN. Nucleoside analogs blocked ruxolitinib-mediated production of extracellular virus. Although low-level ZIKV infection occurred in untreated HC and trophoblasts, the produced virus was incapable of infecting naïve Vero cells.  These deficient virions from untreated HC present "thin-coats" suggesting immature virion structure. Blocking Jak 1/2 signaling (with ruxolitinib) restored replication competence as virions produced under these conditions confer CPE in naïve Vero cells.  These data demonstrate that Jak-STAT signaling directly impacts the ability of primary placental cells to produce replication competent virus and is a key gatekeeper in production of mature virions in clinically relevant cells including HC and trophoblasts. Design of targeted agents to prevent ZIKV replication in the placenta should consider Jak 1/2 signaling and the impact of its block on ZIKV infection and subsequent transmission to the fetus.